PENGARUH UKURAN PERUSAHAAN KLIEN DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Berikang, Andreas; Kalangi, Lintje; Wokas, Heince (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The quality of an audit report on a financial statement is very important for shareholders or other third parties in making decisions. The purpose of this study is to examine the effect of client firm size and audit rotation of audit quality. Audit quality uses proxies public accounting firm size, which is measured by dummy variables using the Big Four public accounting firm and Non Big four public accounting firm, the size of the client firm was measured by calculating the natural logarithm of the firms total assets, audit rotation was measured by dummy variable. Population in this research is manufacturing firm listed in Indonesia Stock Exchange from 2012-2015, sampling method used in this research use purposive sampling method. This research is using the logistic regression analysis using SPSS 22 version. The result indicates that: (1) firm client size has significant effect towards audit quality, (2) audit rotation has no effect towards audit quality. Keywords: Audit Quality, Client Company Size, Audit Rotation, Auditor